Estimating global demand for land-based transportation services using the shared socioeconomic pathways scenario framework. (1st September 2022) - Nkiriki, Joan; Jaramillo, Paulina; Williams, Nathan; Davis, Alex; Armanios, Daniel Erian
Abstract: The global demand for transportation is growing owing to accelerated socioeconomic development worldwide. If the current modes of transportation, consisting mostly of personal internal combustion engine vehicles, dominate this growth, greenhouse gas emissions will rise and worsen the climate crisis. A key empirical challenge in understanding the barriers and opportunities for low-carbon transportation systems in developing countries is the lack of demand data. Because existing country-specific transport demand models focus on countries with robust historical datasets, it has been difficult to estimate the service demand for developing countries. To address this limitation, we develop a log–log regression model linking socioeconomic variables with demand for land-based passenger and freight transport services. Using socioeconomic data from the shared socioeconomic pathways (SSPs) developed for climate analysis, we then produce scenario-based estimates for land-based transportation services for 179 countries around the world. The global average annual land-based passenger demand growth rate ranges between 1.3% and 4.1%, while the annual growth rate for land-based freight demand ranges between 3.1% and 3.6% across the 30 years between 2020 and 2050. Middle-income countries in Asia such as India and China, show the highest expected transport demand across all scenarios. Meanwhile, the results suggest that low-income countries in the sub-Saharan African region are likely to experience the largest growth in demand for passenger and freight transport services. These two trends come together at an inflection point around the year 2030. Prior to 2030, the transport demand was the highest in East Asia. After 2030, there is an ascendancy in transport demand in South Asia and sub-Saharan Africa, whereby the cumulative demand share of these two regions reaches near parity with that of East Asia by 2050. Sustainably meeting this growing demand will require the adoption of data-driven transport planning tools and leveraging cross-linkages across other energy sectors such as electricity.